2020
DOI: 10.7759/cureus.8926
|View full text |Cite
|
Sign up to set email alerts
|

Coagulopathy and Hospital Outcomes in Patients With Spontaneous Bacterial Peritonitis: A Call for Action to Improve Care of Inpatients

Abstract: To assess the risk of in-hospital mortality in spontaneous bacterial peritonitis (SBP) with coagulopathy, and to understand the impact of comorbid coagulopathy on length of stay (LOS) and total charges for SBP inpatients. Methods We included adult patients (age, 18-50 years) with a principal diagnosis of SBP using the Nationwide Inpatient Sample (NIS, 2012 to 2014). These patients were further subgrouped by comorbid coagulopathy. The independent sample t-test was used to measure the mean difference in LOS and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…However, with the disease having affected Caucasian individuals at a magnitude several times greater than it has affected Chinese individuals, it is essential to know the ethnicity-related risk of thrombogenic events. Caucasians have higher thrombotic risk than Chinese and other Asian populations, and the risk is even higher in African-American and Hispanic patients in the USA [ 27 29 ]. Consistent with this pattern, a study conducted on COVID-19 coagulopathy in Caucasian patients showed that although the risk of coagulopathy was higher in Caucasians, because the patients included in the study were on low-molecular-weight heparin (LMWH) thromboprophylaxis, they rarely developed overt DIC, and in cases where DIC developed, it was during the later stages of the disease only.…”
Section: Introductionmentioning
confidence: 99%
“…However, with the disease having affected Caucasian individuals at a magnitude several times greater than it has affected Chinese individuals, it is essential to know the ethnicity-related risk of thrombogenic events. Caucasians have higher thrombotic risk than Chinese and other Asian populations, and the risk is even higher in African-American and Hispanic patients in the USA [ 27 29 ]. Consistent with this pattern, a study conducted on COVID-19 coagulopathy in Caucasian patients showed that although the risk of coagulopathy was higher in Caucasians, because the patients included in the study were on low-molecular-weight heparin (LMWH) thromboprophylaxis, they rarely developed overt DIC, and in cases where DIC developed, it was during the later stages of the disease only.…”
Section: Introductionmentioning
confidence: 99%